Virtual Mannequins Retrieval Based on Cluster-based Panoramic Views (Journal of Fiber Bioengineering and Informatics, 2015)
With the rapid development of 3D scanners, graphic accelerated hardware and modeling tools, theapplication of 3D model database is growing in both numbers and sizes, e.g., 3D head and body scandatasets. In this paper, a novel method by using cluster-based panoramic views is proposed for retrieving3D virtual mannequins. First, a Young Chinese Female Virtual Mannequin (YCFVM) database isestablished by analyzing various 3D body scan data; second, panoramic views of virtual mannequins areobtained, and the Fourier and Wavelet features of the panoramic views are extracted; third, a multi-scaleindexing of the YCFVM dataset is generated for fast matching by using fuzzy clustering for the Waveletfeatures; finally, the Fourier descriptor is embedded into the feature matching with the generated indexingfor obtaining more accurate retrieval results. Experiment results show that the proposed method canachieve better retrieval performance than other descriptors used for virtual mannequin retrieval.